Antibiotic Sensitivity of 40 Mycoplasma pneumoniae Isolates and Molecular Analysis of Macrolide-Resistant Isolates from Beijing, China - Zhao, Fei (American Society for Microbiology, 2012)
MICs of eight antibiotics were detected with 40 Chinese Mycoplasma pneumoniae isolates. Thirty-eight isolates (95%) were macrolide resistant. Each macrolide-resistant isolate harbored an A2063G or A2064G point mutation in the 23S rRNA gene. All 40 isolates (100%) were type I strains, but they might have originated from different clones.